A New Approach To Implementing Culturally Responsive Teaching (CRT) in Primary Education - RM, Christina Lestari; Tiawanti; Patras, Yuyun Elizabeth (International Conference on Elementary Education, 2025)
Teachers play a central role in shaping national character, particularly in multicultural societies such as Indonesia. Culturally Responsive Teaching (CRT) has emerged as an approach that effectivelyintegrates students’ cultural backgrounds into the learning process. However, challenges remain in its implementation at the elementary level, including limited teacher understanding, insufficient culturally relevant materials, and inconsistent integration of local culture into curricula. This study aims to analyze current practices of CRT in Indonesian primary schools and propose a new direction for its implementation. A Systematic Literature Review (SLR) of 25 articles (2020–2024) sourced from Google Scholar and GARUDA was conducted using PRISMA guidelines. Thematic synthesis reveals five dominant themes: (1) enhanced student engagement, (2) cultural relevance in character education, (3) teacher–studentcollaboration, (4) supportive school environment, and (5) strengthening of 21st-century skills. The review recommends that CRT at the primary level must prioritize contextual learning grounded in students’sociocultural realities and position culture as a learning resource to prevent marginalization and foster intercultural respect.